Writing the Rape in Post-Conflict Societies of the 1990s: John M. Coetzee and Slavenka Drakulić. Issue 1 (1st January 2018) - Berber, Neval
ABSTRACT: The International Criminal Tribunal for the former Yugoslavia (ICTY) and the Truth and Reconciliation Commission (TRC), beyond their undeniable differences in dealing with post-conflict justice, were influenced by the same "rape as a weapon of war" paradigm in their approach to the abuses of the women's rights. This article examines literary explorations of this paradigm, i.e., how its interpretative patterns have been appropriated, adjusted, and reshaped in As if I Am Not There (1999) by Slavenka Drakulić and in Disgrace (1999) by John M. Coetzee. It points out how literature in post-conflict societies of the 1990s has been used successfully to problematize the victim status in war and conflict situations and to give voice to the silenced aspects of women's rape stories, as well as to signal the limitations of the main legal and commission discourses that rely on a too rigid conception of sexual violence against women.